An invertebrate stomach's view on vertebrate ecology. (2nd August 2013) - Calvignac‐Spencer, Sébastien; Leendertz, Fabian H.; Gilbert, M. Thomas P.; Schubert, Grit
<x xml:space="preserve">Abstract</x> Recent studies suggest that vertebrate genetic material ingested by invertebrates (iDNA) can be used to investigate vertebrate ecology. Given the ubiquity of invertebrates that feed on vertebrates across the globe, iDNA might qualify as a very powerful tool for 21st century population and conservation biologists. Here, we identify some invertebrate characteristics that will likely influence iDNA retrieval and elaborate on the potential uses of invertebrate‐derived information. We hypothesize that beyond inventorying local faunal diversity, iDNA should allow for more profound insights into wildlife population density, size, mortality, and infectious agents. Based on the similarities of iDNA with other low‐quality sources of DNA, a general technical framework for iDNA analyses is proposed. As it is likely that no such thing as a single ideal iDNA sampler exists, forthcoming research efforts should aim at cataloguing invertebrate properties relevant to iDNA retrieval so as to guide future usage of the invertebrate tool box.